The role of dichotomous thinking and rigidity in perfectionism. - Egan, Sarah; Piek, Jan; Dyck, Murray; Rees, Clare (Elsevier Ltd, 2007)
Perfectionism is a complex psychological construct that has been defined in many different ways. Recent conceptualisations of perfectionism have involved dividing the construct into positive and negative components. Negative perfectionism is associated with high emotional distress whereas positive perfectionism is associated with positive affect and lower levels of distress. Although these distinctions have been made it remains unclear as to how distinct the two aspects of perfectionism are particularly in terms of their cognitive profiles. This study investigated two cognitive constructs that have been theoretically linked to perfectionism. Dichotomous thinking and rigidity were examined in three samples (40 clinical participants, 111 athletes, 101 students). As hypothesised, the clinical sample had the highest score on negative perfectionism, however, no differences were observed between groups on positive perfectionism. Dichotomous thinking emerged as the variable most predictive of negative perfectionism, and was less strongly related to positive perfectionism. These results highlight the importance of dichotomous thinking as a cognitive construct worthy of further research to understand negative perfectionism. Implications for the development of cognitive therapy interventions for negative perfectionism are discussed.